1978
DOI: 10.1021/ja00480a076
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing effect of dangling bases on a short RNA double helix as determined by proton nuclear magnetic resonance spectroscopy

Abstract: Communications t o the Editor 3971 exchange of protons and deuterons between aniline and D20. Therefore, no more than 20% of the observed reduction could have occurred via H2. If all of the reduction has occurred via Hg. there would have been observed 59% deuterium incorporation. We have also observed that there is no appreciable exchange between H2 and D20 under similar reaction conditions in the absence of nitrobenzene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 0 publications
4
22
0
Order By: Relevance
“…The reversal in E FRET occurs at lower salt when the construct contains longer 24 bp helices as opposed to 12 bp helices. Although end-fraying may be a concern for such short duplexes, we expect this effect to be more pronounced for the 12 bp construct, where the dye is much closer to the blunt end (fraying at the end closest to the junction is less likely due to the stabilizing effect of the linker (35)). The agreement between the E FRET values for both constructs, at the extremes of salt, suggests that fraying does not contribute substantially to the measured effects.…”
Section: Effect Of Helix Lengthmentioning
confidence: 96%
“…The reversal in E FRET occurs at lower salt when the construct contains longer 24 bp helices as opposed to 12 bp helices. Although end-fraying may be a concern for such short duplexes, we expect this effect to be more pronounced for the 12 bp construct, where the dye is much closer to the blunt end (fraying at the end closest to the junction is less likely due to the stabilizing effect of the linker (35)). The agreement between the E FRET values for both constructs, at the extremes of salt, suggests that fraying does not contribute substantially to the measured effects.…”
Section: Effect Of Helix Lengthmentioning
confidence: 96%
“…We do not have the complete physical-chemical (or combinatorial) tools necessary for such an undertaking. Even in solution, we neglect the 359 Nucleic Acids Research stabilizing effects of Mg+2 ions and of free dangling ends (25,26). Nonetheless, the calculation was exactly carried out within a well defined framework, i.e.…”
Section: The Thermodynamic Approach To Rna Foldingmentioning
confidence: 99%
“…Additional analysis demonstrated that nearly all helix ends in other classes of structured RNAs are involved in end-stacking ( Table S1 ). Provided that helix ends fray [20] , [21] , [22] , such preponderance of end-stacking in structured RNAs reflects its significance not merely in protecting short canonical RNA helices against fraying as indicated by earlier studies [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [27] , [28] , [29] , [30] , [31] , [32] .…”
Section: Resultsmentioning
confidence: 88%
“…Together with basepairing interactions, base-stacking contributes significantly to the stability of DNA and RNA helices [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] . While internal basepairs are stacked on both sides, the ends of RNA secondary structure helices are stacked on their internal side and exposed to the loop side, potentially susceptible to fraying in that their imino protons exchange with solvent [20] , [21] , [22] .…”
Section: Introductionmentioning
confidence: 99%